Radioactivity of Some Soils in the University of Tikrit, Iraq, college of Education for Girls using Solid-State Nuclear Track Detector type CR-39 - Mohammed Saleh, Sarwa Abd Alqader (Iraqi Journal of Science, 2019)
In this research radon concentrations in soil samples of some sites of the College of Education for Women, University of Tikrit, were measured using CR-39 nuclear impact detector. Soil samples were prepared according to classical protocols whereby they were irradiated for a period of 65 days in propagation chambers chemically treated and subjected to optical microscopy to calculate nuclear effects. The results show differences in the concentrations of radon gas in the samples collected from different sites ranging between a lowest value in the location of the department of English and a highest value of in the location of the cafeteria of College compared to the radiation background of due to the geological factors that depend on the type and specifications of the soil, the amount of gases emitted from the soil, the amount of the emergence of radon from the granules of the soil and its spread through the pores of the soil to the outside.